Innovative Investigation and Strategy for Improving the Performance of 70% Alumina Refractory Roofs Against Thermal-Slag Corrosion and Extreme Temperatures in Electric Arc Furnaces (EAF) in the Nickel Matte Production Process - Anggoro Rohadi; Sulistijono Sulistijono; Lukman Noerochim; Sutarsis Sutarsis; Hariyati Purwaningsih (Eduvest - Journal of Universal Studies, 2025)
This study investigates the performance of 70% alumina refractories on the roof of an Electric Arc Furnace (EAF) in the nickel matte smelting process. The methods used include material characterization through X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD), and Scanning Electron Microscopy-Energy Dispersive X-ray (SEM-EDX), thermodynamic simulation using FactSage, and thermal stress simulation based on Finite Element Analysis (FEA). The results of the study show a significant decrease in Al₂O₃ content to below 16% in the corrosion zone, as well as an increase in Fe₂O₃ which triggers the formation of corrosive hercynite (FeAl₂O₄) and magnesium spinel (MgAl₂O₄) phases. FactSage simulations confirmed the stability of these phases at temperatures of 1200–1400 °C. FEA results identified maximum stress concentrations in the central zone of the roof, approaching the strength limit of the refractory material. Based on these findings, the proposed mitigation strategies include: optimizing the brick geometry design to reduce stress (most realistic in the short term), increasing the alumina content and decreasing Fe₂O₃ in the refractory material (potentially effective, but requires economic evaluation), and controlling the furnace temperature distribution (most technically challenging). This study provides a comprehensive approach to designing more reliable and durable EAF refractories.